SYNERGISTIC EFFECTS OF FEEDING AND DEXAMETHASONE ON SERUM LEPTIN LEVELS - LAFERRÈRE, B. (1998)
The objectives of this study were to determine the time course of the stimulatory effect of dexamethasone on serum leptin and whether it depends on food intake. Dexamethasone (4mg) was administered I. V. over 1 minute to healthy human volunteers (n=8) under fasting and feeding conditions (2000 kcal given at three meals over 7 hours). At 10 hours, serum leptin levels were increased only in the fed subjects (delta leptin 10.6±1.6 vs −2.4±1.9 ng/ml, p=0.01, n=8). To assess the interactive effect of food and dexamethasone on serum leptin, a subgroup (n=4) was studied under 4 conditions: 1) dexamethasone/fast; 2) dexamethasone/food; 3) saline/fast; 4) saline/food. Serum leptin declined from baseline under the fasting conditions, with or without dexamethasone. Feeding prevented the drop in serum leptin. In the dexamethasone/food condition, leptin levels rose from baseline after 7 hours and doubled after 10 hours (p<0.05). The rise in serum leptin was significantly greater in the food/dexamethasone condition compared to all other conditions (p<0.05). In summary, dexamethasone has no independent effect on serum leptin in the absence of food intake. Rather, dexamethasone appears to potentiate the food-induced increase in serum leptin. This synergism may be mediated by insulin and/or other factors associated with food ingestion.